Prominent scholars in Islamic economics and allied disciplines: a bibliometric review - Akbar, Mohamed Aslam; Mohd Thas Thaker, Mohamed Asmy; Mohammed, Mustafa Omar; Nik Mat, Nik Hziman; Abd. Aziz, Hassanuddeen (Emerald Group Publishing Ltd., 2025)
Purpose – The purpose of this study is to address the lack of a proper database or finding system for scholars of Islamic economics (IE), as well as the dearth of literature on bibliographic search and trend analyses of scholars in this field. This study aims to adopt a bibliometric review of the bibliography of experts in IE and scholars in disciplines allied to IE. Design/methodology/approach – This study adopts a bibliometric review of the bibliography of experts in IE and scholars in disciplines allied to IE. The researchers collected data on scholars’ profiles and scholarly works and analyzed them to identify trends and patterns. Findings – This study presents two main themes: the profiles of the scholars in IE and allied disciplines, and their scholarly works. The findings on the scholars’ profiles reveal that most scholars are contemporaries born between the 1940s and 1990s, concentrated in Malaysia and affiliated with the International Islamic University Malaysia. Regarding their scholarly works, the majority of their efforts resulted in 11,736 materials in the form of books, articles and conference papers spread across 13 sub-areas in IE. Originality/value – This study fills the gap in literature by providing a database and finding system for scholars in IE and conducting a bibliographic search and trend analysis of scholars in this field. The findings shed light on the profiles of scholars and their scholarly works, which can guide future research in this area.